Progress on molecular mechanism of aluminum resistance in rice - Jingguang, Chen; Qi, Lai; Baiquan, Zeng; Guo, Longbiao; Ye, Guoyou (Elsevier, 2020)
Aluminum (Al) toxicity in acid soils is a significant limitation to crop production worldwide, as 13% of the world's rice is produced in acid soil with high Al content. Rice is likely the most Al-resistant cereal and also the cereal, where Al resistance is the most genetically complex with external detoxification and internal tolerance. Many Al-resistance genes in rice have been cloned, including Al resistance transcription factor 1 (ART1) and other transcription factors, organic acid transporter genes, and metal ion transporter gene. This review summarized the recent characterized genes affecting Al tolerance in rice and the interrelationships between Al and other plant nutrients.